Temperature effects on the reproductive performance of Aedes aegypti (Diptera: Culicidae) mosquitoes in Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2024)
Abstract not availableBangladesh J. Zool. 51(3): 361-369, 2023